MUHAMMAD SHAHRUR AS A CONTEMPORARY MUSLIM INTELLECTUAL: A PRELIMINARY EXPLORATION - Latif, Muhaemin (Jurnal Diskursus Islam, 2020)
This article seeks to understand Muhammad Shahrur as a contemporary Muslim intellectual in the twentieth century. This finding suggests that Muhammad shahrur was a controversial scholar among Intellectual Muslim. Some allegations led him as the most popular intellectual in this century. A series of books written came to support as well as to counter his ideas on al-Qur’an. This paper review the initial exploration of Muhammad Sharur's work on interpreting al-Qur'an. Besides demonstrating the biography of Muhammad Shahrur, especially, his academic background, the author also reviews at least three important books written by Muhammad Shahrur which become the main issue of this article. Those three books generate a revolutionary idea, especially how to interpret al-Qur'an from a different perspective. Through science methodology as well as language proficiency, Muhammad Shahrur presents the new face of interpreting al-Qur'an. He attempted to read al-Qur'an with the current way of thinking without looking back at the legacies (turats) of Muslim intellectuals.